The ’Aqidah in the Discourse of Sayyid Qutb - Ushama, Thameem (Afkar: Jurnal Akidah dan Pemikiran Islam, 2007)
The paper analyzes Sayyid Qutb’s understanding of the ’aqidah which is the foundation of the Islamic worldview. The study is timely for there are some allegations that Qutb deviates from true ’aqidah and becomes an exclusivist in his interpretations. It gives a brief account of his methodology and examines some of the allegations that his interpretation does not conform to Salaf by differing with early scholars on the meaning of tawhid al-’uluhiyyah and al-rububiyyah. The discussion covers such issues as practices as pre-condition for iman, denying the role of reasoning, criticism of ’ilm al-kalam, the view that iman neither increases nor decreases, denying the authority of khabar ahad, charges that both rulers and individual Muslims as infidels, al-Mu’tazilah doctrine as non-Islamic, Prophet Jesus died before his ascension, and al-Khawarij.